Low cancer prevalence in polyglutamine expansion diseases. (21st March 2017) - Coarelli, Giulia; Diallo, Alhassane; Thion, Morgane Sonia; Rinaldi, Daisy; Calvas, Fabienne; Boukbiza, Ouahid Lagha; Tataru, Alina; Charles, Perrine; Tranchant, Christine; Marelli, Cecilia; Ewenczyk, Claire; Tchikviladzé, Maya; et al.
Abstract : Objective: Polyglutamine (PolyQ) diseases are dominantly transmitted neurologic disorders, caused by coding and expanded CAG trinucleotide repeats. Cancer was reported retrospectively to be rare in patients with PolyQ diseases and we aimed to investigate its prevalence in France. Methods: Consecutive patients with Huntington disease (HD) and spinocerebellar ataxia (SCA) were questioned about cancer, cardiovascular diseases, and related risk factors in 4 university hospitals in Paris, Toulouse, Strasbourg, and Montpellier. Standardized incidence ratios (SIR), based on age- and sex-adjusted rate of the French population, were assessed for different types of cancer. Results: We questioned 372 patients with HD and 134 patients with SCA. SIR showed significantly reduced risk of cancer in HD: 23 observed cases vs 111.05 expected ones (SIR 0.21, 95% confidence interval [CI] 0.13–0.31), as well as in SCA: 7 observed cases vs 34.73 expected (SIR 0.23, 95% CI 0.08–0.42). This was surprising since risk behavior for cancer was increased in these patients, with significantly greater tobacco and alcohol consumption in patients with HD vs patients with SCA ( p < 0.0056). There was no association between CAG repeat size and cancer or cardiovascular disease. However, in patients with HD, skin cancers were more frequent than expected (5 vs 0.98, SIR 5.11, 95% CI 1.65–11.95). Conclusions: There was a decreased cancer rate in PolyQ diseases despite high incidence of risk factors. Intriguingly, skin cancer incidence was higher, suggesting a crosstalk between neurodegeneration and skin tumorigenesis.